THE EFFECT OF ECONOMIC GROWTH, EDUCATION LEVEL, AND PER CAPITA INCOME ON EXTREME POVERTY IN KUNINGAN REGENCY, INDONESIA (2013–2022) - Octaviani, Risthi Dwi; Yusuf, Ayus Akhmad; Bakhri, Syaeful (Cirebon International Journal of Economics and Business, 2025)
The level of extreme poverty is influenced by several factors, namely education, health, per capita income, economic growth. From these factors, researchers conducted research on 3 (three) factors, namely economic growth, education level and per capita income that influence the level of extreme poverty. This study uses a quantitative research approach using secondary data from the BPS of Kuningan Regency for the period 2013-2022. The data analysis technique uses multiple linear regression tests. The results of this study indicate that economic growth has a positive and significant effect on the poverty rate in Kuningan Regency. Education level has a positive and significant effect on the extreme poverty rate in Kuningan Regency. Per capita income has a positive and significant effect on the extreme poverty rate in Kuningan Regency. As well as economic growth, education level and per capita income have a positive and significant effect on the extreme poverty rate in Kuningan Regency with a calculated F value of 158.938 > F table 4.760 with a significant value of 0.000 < 0.05.The coefficient of determination (adjusted R Square) showed a percentage of 41.4%, indicating that economic growth, education level, and per capita income significantly influence the level of extreme poverty. The remaining 58.6% is influenced by other factors not mentioned in this study.